Apprezzare altre menti - Marchetti, Luca (Scenari, 2024)
This paper addresses the issue of whether other animals’ minds can be legitimate objects of aesthetic appreciation. It argues that (a) we can appreciate other minds; (b) that the object of appreciation in these cases is twofold: on the one hand, we appreciate the fitness, peculiarities, differences, and subtleties of the workings of other minds and, on the other, we appreciate the imaginative activity of trying to put ourselves in the animal’s perspective; and (c) that, as a consequence of (b), the nature of our appreciation is also twofold: on the one hand, it is an experience of the aesthetic qualities that emerge from what we know about the workings of other minds and, on the other, we derive pleasure from the challenging imaginative effort involved in trying to put ourselves in the animal’s perspective, rather than from achieving a definitive result.